Cholangioscopy in the digital era - Ayoub, Fares; Yang, Dennis; Draganov, Peter V. (Translational Gastroenterology and Hepatology; Vol 3 (October 2018): Translational Gastroenterology and Hepatology, 2018)
Cholangioscopy allows direct visualization and subsequent therapeutic maneuvers of the biliary ductal system. With advances in endoscopic and imaging technology, cholangioscopy has become an important modality for the diagnosis of indeterminate biliary strictures and an essential therapeutic tool for difficult to remove biliary stones. Enhanced imaging and operability of the latest generation cholangioscopes have further expanded their clinical applications to include ductal tumor ablation, gallbladder drainage, access to difficult to reach branches of the biliary tree, and biliary foreign body manipulation. In this review, we discuss the technical evolution of cholangioscopy into the digital era and review the clinical evidence supporting its use in the diagnosis and therapy of biliary tract disease.